The Influence of Service Personalization, Customer Satisfaction, and Customer Retention in the Telecommunications Industry on Data-Driven Marketing - Muh Fihris Khalik; Wily Mohammad; Zilfana Zilfana; Orfyanny Syahreffy Themba (Westscience Press, 2023)
This research investigates the intricate dynamics of service personalization, customer satisfaction, and customer retention in the context of the telecommunications industry and their influence on data-driven marketing effectiveness. A quantitative approach, employing Structural Equation Modeling with Partial Least Squares (SEM-PLS), was utilized to analyze survey data from a sample of 250 participants. The study confirms the reliability and validity of measurement instruments, establishes discriminant validity, and unveils significant positive relationships between customer retention, customer satisfaction, service personalization, and data-driven marketing effectiveness. The findings underscore the importance of personalized services and customer-centric strategies in enhancing marketing outcomes within the telecommunications sector. The high explanatory power of the model emphasizes the relevance of these factors in shaping the landscape of data-driven marketing in the digital age.